Pengaruh Bekukan (Robek, Kusut dan Rekatkan) Activity Terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun - Isnaningsih, Anti; Khomsatun Nur Laela (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to determine the effect of freeze (tear, tangle, and glue) activity on fine motor skills at Pertiwi Sri Hastuti Kindergarten, Simbang Village, Banjarnegara Regency. This study was motivated by motor skills at Pertiwi Sri Hastuti Kindergarten, Simbang Village, which still need improvement or have not developed according to their age stages. This study is an experimental study of the quasi-experimental design type with pre-test, treatment, and post-test stages. The sample in this study were 58 children aged 5-6 years. The data collection method used in this study was observation. The data analysis techniques used were validity, reliability, homogeneity, normality, and effectiveness tests. The results showed that there were changes in fine motor skills after 12 treatments. The freeze (tear, tangle, and glue) activity treatment had an effect on fine motor skills in this problem. Based on the data analysis that has been done, it is known that the mean pre-test value is 17.8857 while the mean post-test value increased to 20.8857. Thus, there was an average increase of 16.77% from the freezing activity. This can be concluded that the results of the post-test implementation showed a better change in fine motor skills, which means that the freezing (tearing, crumpling, and gluing) activity affected fine motor skills in children aged 5-6 years.